(untitled) (In situ, 2025)
The investigation of the shipwreck near Mali Školj has once again proven to be highly engaging this year. Many new structural elements of the vessel have been uncovered, including a series of deck beams and two longitudinal reinforcements. Notably, the stern of the ship has now been reached. In the central section, researchers discovered 14 round objects made of copper sheet, whose purpose remains unknown, as well as 72 stone cannonballs of five different calibres. Continued systematic research is essential for enhancing our understanding of Late Renaissance shipbuilding in the Dubrovnik Republic and its allies.